The use of collaborative strategic reading (CSR) in English reading comprehension class: A study among undergraduate students in Aceh - Hermida, Rita (Accentia: Journal of English Language and Education, 2023)
Some students consider that reading comprehension is still one of the most challenging subjects in English. Others find topics covered while reading English books to be uninteresting. Teachers attempt to address these issues by utilizing a variety of strategies that boost students' reading comprehension abilities. Collaborative Strategic Reading (CSR) is one strategy used to help solve these issues. This study investigated the use of CRS in reading comprehension among undergraduate students. The study was carried out at English Language Education Department of Universitas Islam Negeri (UIN) Ar-Raniry Banda Aceh. This study used quantitative research method namely pre-experimental research design in which the class chosen was only one class consisting of 32 students and given the pre-test, teaching presentation, and post-test. The treatment was the CSR as the method during four times meetings in reading comprehension class. The mean score of the pre-test was 62.1 while, the mean score of the post-test was 77.3. The study concluded that the CRS strategy had a postive impact to the students reading comprehension as seen from the increase of test scores. The use of CSR is therefore useful in teaching reading for students at the university level.